Long-Term Changes in the Abundance of Benthic Foraging Birds in a Restored Wetland - Mander, Lucas; Scapin, Luca; Thaxter, Chris B.; Forster, Rodney M.; Burton, Niall H. K. (Frontiers in Ecology and Evolution, 2021)
Estuaries have historically been subject to considerable habitat loss, and continue to be subjected to such in areas where the natural landward migration of intertidal habitats is constrained by hard coastal defences. Thus, in estuaries where direct (e.g., port development) or indirect (e.g., sea level rise) processes are predicted to threaten intertidal habitats and associated waterbird species, there is a regulatory requirement to produce compensatory intertidal habitats. Managed realignment (MR) is a shoreline management practise that is undertaken to build sustainable coastal defences and create intertidal habitats in estuaries. This nature-based solution brings multiple benefits in the form of carbon storage, increased resilience to flooding, and, potentially, the formation of new habitats, which is the topic of this study. A 75-ha site at the Paull Holme Strays (Humber Estuary, United Kingdom) was monitored over a 10-year period following MR to examine the change in the abundance of waterbirds in the chosen site in response to the physical processes occurring there. Using digital terrain models (DTMs) collected via light detection and ranging (LiDAR), we examined how four compensatory target species responded to changes in elevation after the creation of the site. It was shown that the very rapid accretion of estuarine sediment occurred in the first decade of the new re-created intertidal, which, over time, led to changes in the numbers of benthic foraging birds supported. Furthermore, elevation change was also driven by this sediment accretion, the rate of which depended on the initial bed elevation of the sectors within the site. Ten years after the recreation of the habitat, the spatial heterogeneity in the bed elevation remained high; however, the sectors with the lowest elevations accreted the most over the 10-year period. The foraging number of the four waterbird species that colonised the MR site significantly declined above a certain elevation, with this effect being most pronounced for the Eurasian curlew (Numenius arquata). The number of common shelducks (Tadorna tadorna), dunlins (Calidris alpina), and common redshanks (Tringa totanus) declined significantly after initial peaks 5–7 years after the creation of the site, reflecting the ongoing elevation changes. Thus, this study highlighted the need for long-term studies to understand how species respond to large-scale habitat construction. It can also aid in predicting the suitability of an MR site for waterbirds in the medium and long term.